4CPS-093 Long-term efficacy of second-generation direct-acting antiviral agents (daas-2) for hcv treatment: a meta-analysis. (2nd March 2018) - Inserra, C; Davies, SE Campbell; Bignamini, A; Minghetti, P
Abstract : Background: Efficacy of second-generation direct-acting antiviral agents (DAAs-2) in terms of sustained viral response (SVR) 12 weeks after the end of treatment (EOT) has widely been proven. 1–5 However, long-term efficacy is still controversial due to the low number of available studies with a small number of patients. Purpose: The objective of the study is to conduct a systematic review and, if possible, a meta-analysis of existing clinical evidence in terms of long-term efficacy (SVR longer than 12 weeks after EOT) of DAAs-2 for HCV treatment. Material and methods: A systematic review was performed with the use of CENTRAL, MEDLINE, Embase, Pubmed and SBBL-CILEA/METACRAWLER databases. Trials were initially screened by the title. Second, full papers and abstracts were analysed. The meta-analysis included randomised controlled trials (RCTs) with adult patients affected by HCV, treated with DAAs-2 and assessed for longer than 12 weeks after EOT. Study quality assessment was undertaken using the Jadad scale. Heterogeneity analysis of the studies was conducted with Chi-square and I 2 : the statistical analysis of the efficacy rate was performed using the meta package with the R software 6. The effect estimate was expressed in risk ratio (RR) with 95% confidence interval (CI 95%) and pooled using a random effects model. Results: Of the 106 identified studies, 11 high-quality RCTs were included for meta-analysis (25 were duplicate publications, 70 did not meet the inclusion criteria). Considered genotypes were 1 (nine), 2 (one) and 3 (one). Meta-analysis included 3720 patients (2698 treated with DAAs-2; 1022 treated with placebo or a first-generation DAA±ribavirin± PEG-interferon). Heterogeneity between studies was high (p<0.001; I 2 =90.2%), however it was absorbed by the model (t 2 =0.08). Long-term efficacy was expressed as SVR 24 weeks after EOT, since longer timescales were not available. According to the pooled RR, the incidence of efficacy was 1.5 (95% CI: 1.24 to 1.83, p<0.001). Conclusion: The meta-analysis demonstrated that DAAs-2 for HCV treatment have long-term efficacy at SVR 24 weeks after the EOT. However, the number of studies is mostly based on genotype 1. More RCTs are required to confirm long-term efficacy at more than 6 months after EOT for all treated genotypes. References and/or Acknowledgements: 1. https://www.epatitec.info/terapie/terapia-ledipasvir-sofosbuvir/efficacia-terapeutica 2. https://www.epatitec.info/terapie/terapia-ombitasvir-paritaprevir-dasabuvir/efficacia-terapeutica 3. https://www.epatitec.info/terapie/terapia-daclatasvir/efficacia-terapeutica 4. https://www.epatitec.info/terapie/terapia-simeprevir/efficacia-terapeutica 5. https://www.epatitec.info/terapie/terapia-sofosbuvir/efficacia-terapeutica R Foundation for Statistical Computing (Version 3.3.3). No conflict of interest